sister now : s, richard now: s-3If Richard is 3 years younger than his sister, how old will Richard be in 5 years?
st 1. 2(s-3-2) = s-2
St 2. s-2=2(s-3)
Could somebody help? whats wrong with my statements and logic?
Given: r=s-3. Question: r+5=s+2=?
(1) Two years ago Richard was twice as young as his sister --> 2*(s-3-2)=s-2 --> s=8 --> r+5=s+2=10. Sufficient.
(2) If Richard's sister were born 2 years earlier, she would now be twice as old as Richard --> if Richard's sister were born 2 years earlier she would now be s+2 years old not s-2, so s+2=2(s-3) --> s=8 --> r+5=s+2=10. Sufficient.
Can you provide more detail in the steps of statement 1 and 2. I know you're using some shortcuts but I can't seem to follow.